A review on information communication technology adoption in the Nigerian healthcare sector - Ahamat, Amiruddin; Ayeyi Victoria Sumbabu, Gyebo; Yahaya, Siti Norbaya (Inderscience Enterprises Ltd, 2022)
Studies on information communication technology (ICT) adoption in the Nigerian healthcare sector posit that the objective of encouraging information sharing throughout all public hospitals in Nigeria is still far-fetched following the limited number of hospitals that utilise ICT in their everyday clinical and administrative operations. The proposed study is framed under four objectives, which seek to critically examine existing literature on the issue, recognise obstacles to ICT adoption in Nigeria, consider the context of the administrative policy during and post ICT adoption, and suggest potential solutions that can be implemented by the Federal Ministry of Health Nigeria as part of the effort to introduce ICT to improve the service quality within the sector. This study conducted a systematic review of relevant literature using the ATLAS.ti 9 software. The result demonstrates that the current environment recognises the value of information and communication technology to improve the healthcare sector.